The development of Islamic economics in the Malay Lands: a historical study and economic practice - Selamat, Muhammad Isa (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to examine the historical development of Islamic economic civilization in the Malay Lands and analyze how Islamic economic values ​​and institutions are applied in the socio-economic practices of local communities. Method – Using a descriptive qualitative approach and library research methods, this study traces historical sources, classical manuscripts, and scientific literature that discuss the Islamic economic system in regions such as the Sultanates of Malacca, Aceh, Johor, and Kedah. Findings – The study results show that the Islamic economic system has been firmly integrated into the social structure of Malay society through the practices of zakat, waqf, baitul mal, and Islamic trade ethics based on justice and social welfare. These institutions are not only mechanisms for distributing wealth but also act as instruments of da'wah and strengthen public morals. However, the main obstacles to revitalizing the system are modern challenges such as secularizing the economic system, limited sharia regulations, and the dominance of the capitalist model. Implications – The implications of this study emphasize the importance of the reconstruction of Islamic economics that is not only normative but also contextual and operational to be able to answer the needs of contemporary society sustainably.